High-energy charged particles : their chemistry and use as versatile tools for nanofabrication /: their chemistry and use as versatile tools for nanofabrication. (2015) - Seki, Shu; Sakurai, Tsuneaki; Omichi, Masaaki; Saeki, Akinori; Sakamaki, Daisuke
No abstract available